Long Term Continuous Positive Airway Pressure and Non-invasive Ventilation in Obstructive Sleep Apnea in Children With Obesity and Down Syndrome - Verhulst, Stijn (Frontiers in Pediatrics, 2020)
This review will focus on non-invasive ventilation (NIV) and continuous positive airway pressure (CPAP) therapy in children with obesity and underlying syndromes. These children have a high prevalence of obstructive sleep apnea (OSA) and residual OSA after adenotonsillectomy. Therefore, a high proportion of these children are treated with CPAP or NIV. This review will focus on treatment selection tools and will subsequently cover specific issues on CPAP treatment in obese and syndromic children with a major focus on Down syndrome.